FROM MAGMATIC TO METAMORPHIC DEFORMATIONS IN A JURASSIC OPHIOLITIC COMPLEX: THE BRACCO GABBROIC MASSIF, EASTERN LIGURIA (ITALY) - Menna, Francesco (Ofioliti, 2009)
A new structural study with multiscale detailed analysis of the main elements of the fabric was performed on the Bracco ophiolitic massif (Eastern Liguria). The results are here presented with a reconstruction of the sequence of events which characterized the evolution of the gabbroic complex, starting form the first magmatic phases up to the late metamorphic ones, through a retrograde path which ended with the final exposure of the gabbro on the ocean floor. The field observations, supported by petrographic analyses, lead to outline for the Bracco Gabbroic Complex a deformative evolution which started in the early magmatic phases; the study of the metamorphic structures, following the intrusion and the syn-magmatic deformation of the gabbroic complex, allowed to identify three distinct metamorphic phases, whose petrographic features show that the associated deformations could actually represent a continuous evolution of the same tectonic phenomenon, which started under granulitic facies conditions, continued in amphibolitic facies and ended with deformations and recrystallizations in greenschist facies conditions.